2020
DOI: 10.1093/ofid/ofz553
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Vancomycin-Resistant Enterococcus faecium and Enterococcus faecalis Colonization in Nursing Facilities

Abstract: Background Vancomycin-resistant Enterococcus faecium and Enterococcus faecalis frequently colonize nursing facility (NF) residents, creating opportunities for vancomycin-resistant Enterococcus (VRE) transmission and dissemination of mobile genetic elements conferring antimicrobial resistance. Most VRE studies do not speciate; our study addresses this lack and compares the epidemiology of E faecium and E faecalis. Methods We e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 37 publications
2
16
0
Order By: Relevance
“…This conforms to a report from a study from the United States that reported a higher prevalence of E faecium from clinical settings. 39 Many studies around the world have, however, reported the predominance of E faecalis in clinical infections. 40 – 42 Differences in the geographical region can be a major factor in this variation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This conforms to a report from a study from the United States that reported a higher prevalence of E faecium from clinical settings. 39 Many studies around the world have, however, reported the predominance of E faecalis in clinical infections. 40 – 42 Differences in the geographical region can be a major factor in this variation.…”
Section: Discussionmentioning
confidence: 99%
“… 43 An increase in E faecium prevalence in clinical infections have been linked to increase in the use of medical devices and increased duration of carriage. 39 …”
Section: Discussionmentioning
confidence: 99%
“…Because resistance to vancomycin is more regular in homogenous E. faecalis , administering of beta lactams should be at the forefront before the use of conventional culture [ 56 ]. Arias and Murray [ 57 ] and Davis et al [ 58 ] stated that most VRE infections were caused by E. faecalis . This has changed as more VRE caused by E. faecium are increasingly being reported [ 59 , 60 , 61 ] because of their resistance to different group of antibiotics which are mostly expensive [ 62 , 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…These bacteria are known as the fourth leading cause of nosocomial infections, the third leading cause of bacteremia infections, and the second leading cause of urinary tract infections [5] . Various studies have shown antibiotic resistance of this bacterial species [6] . Proteus bacilli are also optional Gram-negative bacilli belonging to the group of Proteobacteria and aerobic anaerobes [7] .…”
Section: Introductionmentioning
confidence: 99%